2022
DOI: 10.1002/ppul.25821
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with successful extubation following the first course of systemic dexamethasone in ventilator‐dependent preterm infants with or at risk of developing bronchopulmonary dysplasia

Abstract: Objectives: We aimed to identify factors present at the start of an initial course of systemic dexamethasone that would be associated with successful extubation in mechanically ventilated neonates <30 weeks gestational age (GA) with or at risk of developing bronchopulmonary dysplasia (BPD).Methods: We studied a retrospective cohort of neonates (23 +0 −29 +6 weeks GA), with or at risk of developing BPD, prescribed their first course of systemic dexamethasone to aid in extubation from mechanical ventilation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In several previous studies, low pre-extubation FiO 2 has been reported as predictive of extubation success 9 18 25. We suggest that a cut-off for pre-extubation FiO 2 at ≥0.35 is a clinically relevant predictor indicating a high risk for extubation failure.…”
Section: Discussionmentioning
confidence: 47%
“…In several previous studies, low pre-extubation FiO 2 has been reported as predictive of extubation success 9 18 25. We suggest that a cut-off for pre-extubation FiO 2 at ≥0.35 is a clinically relevant predictor indicating a high risk for extubation failure.…”
Section: Discussionmentioning
confidence: 47%
“…As both studies are comparable and an online calculator (http:// extubation.net/) exists, I think using this tool would be much easier, but I do agree with O'Connor et al 1 that we need to develop a prognostic scoring model for intubated preterm infants.…”
mentioning
confidence: 66%
“…To the Editor, I read with great interest the article by O'Connor et al 1 describing factors that lower the likelihood of successful extubation by Day 14 in mechanically ventilated neonates with or at risk of developing bronchopulmonary dysplasia born at <30-week gestational age (GA).…”
mentioning
confidence: 99%
See 2 more Smart Citations